"Looking Up and Feeling Down". The influence of mobile social networking site use on upward social comparison, self-esteem, and well-being of adult smartphone users. (September 2019) - Schmuck, Desirée; Karsay, Kathrin; Matthes, Jörg; Stevic, Anja
Highlights: First study to explore longitudinal effects of mobile SNS use on adults' well-being. Facebook use significantly predicts upward social comparison across all age groups. Upward social comparison harms individuals' self-esteem and well-being over time. Instagram use has a direct negative influence on well-being over time. Abstract: Exposure to carefully selected information on social networking sites (SNSs) showing a flawless self and an ideal life has been found to harm young individuals' self-esteem and well-being. However, SNS use is no longer limited to young people. Fueled by the sharp increase of smartphone ownerships, which allow users to access information about others anytime and anywhere, nowadays, a wide range of age groups uses SNSs. Accordingly, this study investigated the relationships between mobile SNS use, upward social comparison, self-esteem, and well-being for the first time. We employed a two-wave panel survey ( N T2 = 461) using a quota sample of adults. Results revealed that Facebook use predicted upward social comparison, which harmed individuals' self-esteem and well-being over time, while Instagram use directly influenced well-being negatively over time. Additionally, we found support for reciprocal relationships between upward social comparison on SNSs and self-esteem as well as well-being in a longitudinal context. The potential negative implications of SNS use on well-being are discussed.